Mentoring : a Henley review of best practice - Cranwell-Ward, Jane.; Bossons, Patricia; Gover, Sue; Henley Management College (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2004)
This book draws upon valuable case study material and includes advice on best practice from leading companies on setting up, running and evaluating mentoring schemes. The book is an easy-access compendium of collected wisdom with a multitude of insights, ideas and shared experience from the most successful and effective mentoring schemes.
Replicates the experience of attending a Focus Group meeting like those held by the Henley Learning Partnership, which was set up by Henley Management College in 1995.
Includes bibliographical references (p. 250-251) and index.
obn 02/10/2018
Loans
Keywords: Mentoring in business; Mentoring in the professions; Organizational learning